Better tractor wheels - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The National Institute of Agricultural Engineering at Silsoe, UK, is trying to develop tractor wheels that can be used efficiently in the slippery conditions of paddy fields. A paddy field has been constructed at Silsoe and scientists are planning...